The underfoot. Book 1, The mighty deep - Fisher, Ben, 1976-; Whitten, Emily S. (Caracal [an imprint of] Lion Forge Comics, 2019)
"It has been untold years since the Giants-That-Were disappeared, leaving behind the animals forever changed by their strange science. Now, granted the gifts of intelligence and self-awareness, the valiant Hamster Aquatic Mercenaries struggle to keep their horde alive in the dangerous new world. H.A.M. has been hired to save their badger allies from dangerous flooding, but first they'll need new recruits."--Provided by publisher.